Low incidence of acute rejection in hepatitis B virus positive liver transplant recipients and the impact of hepatitis B immunoglobulin - Veerappan, Annapoorani (Hum Immunol, 2016)
Historically, hepatitis B virus (HBV) liver transplantation (LT) recipients have less acute cellular rejection (ACR) than those without HBV. We questioned whether this has persisted in an era of decreased Hepatitis B immunoglobulin use (HBIG) given its in vitro immunoregulatory effects. We compared the incidence, risk factors and outcomes of ACR among 40,593 primary LT recipients with HBV, hepatitis C, steatohepatitis, and immune liver disease (OPTN 2000–2011). We also assessed the in vitro effect of HBIG on alloimmune lymphoproliferation and regulatory T cell generation using mixed lymphocyte reactions. In multivariate analysis, HBV status remained a strong independent predictor of freedom from ACR (OR 0.58, 95% CI: 1.5–2.1). Patient (67.7% vs 72.3%) and graft (60.8% vs 69.1%) survival were significantly lower in patients with ACR versus no ACR for all causes except HBV. HBIG use had no statistical association with ACR. In vitro, HBIG at concentrations equivalent to clinical dosing did not inhibit lymphoproliferation or promote regulatory T cell development. In summary, the incidence and impact of ACR is lower now for HBV LT and does not appear to be secondary to HBIG by our in vitro and in vivo analyses. Rather, it may be due to the innate immunosuppressive properties of chronic HBV infection.